Climate change and economic crisis: how to reduce both - García Fernández, Cristina (Nómadas. Critical Journal of Social and Juridical Sciences, 2017)
Today we have several preventive economic policies that are designed to reduce emissions of greenhouse gases (GHG). The existing literature usually defines these policies as cost-efficient for they can achieve a significant reduction in emissions without having to incur in a very high cost. Likewise, these policies are also cost effective provided that they not only achieve significant cuts in emissions of the most released gas in the atmosphere, but also other greenhouse gases. For example, increasing energy efficiency not only reduces carbon dioxide emissions but also other gases that highly contribute to global warming. In addition, greater efficiency can make industries and countries become more competitive in international markets. In the current context of economic crisis the level of efficiency becomes even more important. We need to be efficient to save on costs and to produce with more sustainably but this goal cannot be achieved without changing the current production model. The carbon tax is an incentive that has a double advantage. First, it is an efficient option to palliate climate change as it is able to achieve emission reductions without incurring in excessive costs. Second, is in itself, an incentive to achieve a gradual change towards a more sustainable production system, which is no doubt a claim for the current crisis. The purpose of this paper is, therefore, to analyze the case of the carbon tax, for being the incentive that implements greater efficiency in the market and for constituting an effective option for palliation the current global crisis negative effects.